1932
DOI: 10.1021/ja01344a011
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Decomposition of Hydrogen Peroxide by the Iodine-Iodide Couple at 25°

Abstract: pendence of the rate of reaction and the explosion limit on size of vessel, activity of the wall, inert gases and temperature, have been investigated. The reaction affords another example in which chains are initiated at the wall and are propagated thence into the gas phase. In the proposed mechanism the OH radical is believed to be the carrier in these reaction chains.The effect of hydrogen chloride on the bromine sensitized ozone decomposition and its reaction with ozone have been studied. Very small amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 1 publication
2
59
0
1
Order By: Relevance
“…It is already known that the decomposition of hydrogen peroxide follows first order kinetics with respect to itself [1,[3][4][5]7,8,10,11]. Also, it has been shown that the concentration of hydrogen peroxide at the termination of the oscillatory period is approximately the same in every rtm (or oscillogram) performed at different initial hydrogen peroxide concentrations with constant other parameters [7,8,11].…”
Section: Resultsmentioning
confidence: 99%
“…It is already known that the decomposition of hydrogen peroxide follows first order kinetics with respect to itself [1,[3][4][5]7,8,10,11]. Also, it has been shown that the concentration of hydrogen peroxide at the termination of the oscillatory period is approximately the same in every rtm (or oscillogram) performed at different initial hydrogen peroxide concentrations with constant other parameters [7,8,11].…”
Section: Resultsmentioning
confidence: 99%
“…If additional side reactions occur, then less OH is available for reaction (43), which implies less CH3 is created. This in turn reduces the production of CH3I in Eq.…”
Section: Organic Iodide In Aqueous Solutionmentioning
confidence: 99%
“…Since the pioneering work of Bray and Liebhafsky (BL) on the oscillation reaction of iodine and hydrogen peroxide, the oxidation reaction of iodine to iodate has received significant attention [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%